Kontribusi Pemikiran Hasbi Ash-Shiddieqy dalam Bidang Fikih - Aan Sufian (Media Syari'ah, 2012)
Hasbi Ash-Shiddieqy (1904-1975) argued, Muslims should be able to distinguish between the Shari’ah which directly from Allah SWT, and fiqh, which is the interpretation of the Shari’a by the mujtahid scholars. So far, there is an impression that Muslims in Indonesia tend to regard fiqh as a Shari’a jurisprudence that should be applied absolutely. As a result, the books of fiqh regarded as a source of religious law, although the Islamic legal opinions of the school sometimes are—to some how—incompatible with the current context. Hasbi saw the need to do ijtihad (Islamic exertion) in favoring the benefit for the people in response to the flow of modernization because Islamic law can basically meet public needs and the needs of mankind. Hasbi offered muqaranah (comparative) method which applied not among the Islamic schools, but also between schools and modern legislation. Hasbi offered idea ijtihad jama’i (ijtihad collectively) by engaging and involving various Muslim scientists so that decisions made are closer to the truth and a much more in line with the demands of the situation and welfare of the community. Since 1940, Hasbi offered the need for having Indonesian fiqh to be a pillar for the development of the Indonesian law. Through ijtihad collectively, according to Hasbi, Indonesian Muslims could formulate and have fiqh according to the personality of the Indonesian nation